Off-season vegetable cultivation under low tunnel technology in Bikaner District of Rajasthan: An economic analysis - Rani, Rekha; Meena, SR; Choudhary, BR; Jatav, MK; Saroj, PL; Meena, Anita (Vegetable Science, 2022)
The arid western part of Rajasthan is well known for Indian segment of the Thar Desert. The hot arid regions of India cover 31.7 million hectares, with the majority of the area (61.9%) located in Rajasthan. In Rajasthan, the region is spread over 12 districts including Bikaner. The region is characterized by harsh climatic conditions. In such a situation, protected structures like low tunnels play an important role in vegetable cultivation. Off-season cultivation under protected structures is one of the ways to fulfill demand for vegetables. Although technology can make available better quality vegetable produce around the year but, at the same time it should be economically feasible for the farmers too. The present study was conducted to examine the economics of off-season vegetable cultivation under low tunnel technology in the Bikaner district of Rajasthan. The cost concepts given by Commission for Agricultural Cost and Prices (CACP) were used to calculate the cost of cultivation. Major cucurbits viz bottle gourd, ridge gourd, watermelon, muskmelon, long melon were selected for the study.